2016
DOI: 10.1542/peds.2015-2836
|View full text |Cite
|
Sign up to set email alerts
|

Residential Moving and Preventable Hospitalizations

Abstract: OBJECTIVES: To investigate the association between moving home in the first year of life and subsequent emergency admissions for potentially preventable hospitalizations. METHODS:We undertook a cohort analysis of linked anonymized data on 237 842 children in the Welsh Electronic Cohort for Children. We included children born in Wales between April 1, 1999 and December 31, 2008. The exposure was the number of residential moves from birth up to 1 year. The main outcome was emergency admissions for potentially pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 32 publications
2
8
0
Order By: Relevance
“…Residential mobility, in a low-income population like that which is served by CHCs, has been shown to cause Open access disruptions in health and healthcare. [8][9][10] In this analysis, we also find evidence that such mobility is also associated with reduced routine care utilisation in children with a chronic disease. From these findings we are unable to determine if these children received sufficient or quality care, but the fact that they use less than their counterparts raises concern that this is possible, and clinical organisations and future research could consider further evaluating risk screening strategies that employ number of address changes from administrative data in order to stratify clinical risk.…”
Section: Open Accesssupporting
confidence: 55%
See 1 more Smart Citation
“…Residential mobility, in a low-income population like that which is served by CHCs, has been shown to cause Open access disruptions in health and healthcare. [8][9][10] In this analysis, we also find evidence that such mobility is also associated with reduced routine care utilisation in children with a chronic disease. From these findings we are unable to determine if these children received sufficient or quality care, but the fact that they use less than their counterparts raises concern that this is possible, and clinical organisations and future research could consider further evaluating risk screening strategies that employ number of address changes from administrative data in order to stratify clinical risk.…”
Section: Open Accesssupporting
confidence: 55%
“…A Welsh team, using data from more than 200 000 children, found that moving within the first year of life was associated with increased risk of future emergency hospitalisation for asthma. 8 Other studies from Europe and New Zealand have also found residential mobility to be associated with negative health outcomes 9 10 possibly because moves can be an indication of financial insecurity or other underlying family instability.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work indicated that ≥ 2 home moves for young children were associated with an increased risk of emergency admissions (IRR 1.33, 95% CI 1.18 to 1.51). 53 Therefore, this may be an indication of moving into an unfamiliar home, as opposed to related to the garden paths themselves.…”
Section: The Effect Of the Housing Intervention On Other Health Outcomesmentioning
confidence: 99%
“…This complex cohort enables numerous research questions to be addressed. For example, WECC has revealed factors that increase the likelihood of respiratory admissions up to age 5 years; and that children who move house frequently have an increased risk of poor health and educational underachievement [34][35][36].…”
Section: Noteworthy Outputsmentioning
confidence: 99%